Hidrólise com água subcrítica da casca de soja catalisada por WO3/ZrO2 para conversão de açúcares em plataformas químicas - Gonçalves, Juliana Almeida (2022)
Millions tons of soybean husk are annually produced in Brazil, a lignocellulosic residue which have potential to be utilized as feedstock in the production of sugars (Glucose, Cellobiose, Xylose and Arabinose) and, specially, platform chemicals. 5- hydroxymethylfurfural, furfural, formic acid, acetic acid and levulinic acid are the main biomass-derived chemicals. Therefore, the aim of this study was to assess the conversion of soybean husk into sugars and platform chemicals via subcritical water hydrolysis catalyzed by WO3/ZrO2. The effect of temperature (240 °C and 280 °C) and the presence of WO3/ZrO2 with of 5, 10 and 20% W were assessed in relation to fermentable sugars yield (YFS) and platform chemicals yield (YPC). The higher YPC of 12.91 ± 1.08 g/100g biomass was achieved at 240 °C with WO3/ZrO2 20%W simultaneously to low YPC (4.43 ± 0,21 g/100g biomass), indicating the catalyzed conversion of sugars into platform chemicals. Higher concentration of formic acid, acetic acid and levulinic acid were obtained at 240 °C with WO3/ZrO2 20%W, while higher conversion to 5-hydroxymethylfurfural and furfural was at 280 °C with WO3/ZrO2 20%W. The results confirmed the potential of WO3/ZrO2 catalyzed subcritical water hydrolysis of soybean husk into sugars and platform chemicals.